Aortic Isthmus Retrograde Blood Flow in Intrauterine Child as a Sign of the Terminal Stage of Placental Dysfunction: Clinical Observation - Nodira M. Normuradova (Вопросы современной педиатрии, 2023)
Background. Aortic isthmus retrograde blood flow in intrauterine children with growth delay and centralization of blood circulation in the late stages of placental dysfunction is associated with a high risk of perinatal death. Timely diagnosis of such condition is crucial to select further obstetric tactics and delivery time. Clinical case description. Growth delay and absent end-diastolic flow in umbilical artery and no A-wave in the venous duct were diagnosed in intrauterine child (gestational age — 36 weeks) at ultrasound study. Peripheral resistance indices in middle cerebral artery in the intrauterine child were lower than peripheral resistance indices in umbilical artery. Color Doppler imaging has revealed aortic isthmus retrograde blood flow. The woman was recommended delivery due to critical circulatory disorder in the intrauterine child. Female child was delivered via Caesarean section, child’s weight — 890 g, APGAR score — 3/4. The newborn girl died due to multi-organ failure within the first day.Conclusion. Revealing the retrograde blood flow in intrauterine child in the aortic isthmus throughout the entire ventricular diastole is an unfavorable prognostic sign of the terminal stage of cerebral blood flow disturbance associated with placental dysfunction.